2019
DOI: 10.3390/nano9091198
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Self-Powered Ultraviolet Photodetector Based on Nano-Porous GaN and CoPc p–n Vertical Heterojunction

Abstract: Gallium nitride (GaN) is a superior candidate material for fabricating ultraviolet (UV) photodetectors (PDs) by taking advantage of its attractive wide bandgap (3.4 eV) and stable chemical and physical properties. However, the performance of available GaN-based UV PDs (e.g., in terms of detectivity and sensitivity) still require improvement. Fabricating nanoporous GaN (porous-GaN) structures and constructing organic/inorganic hybrids are two effective ways to improve the performance of PDs. In this study, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, by integration with emerging high-efficiency electrode materials, the GaN-based microwires structures with trap-assisted transport paths hold the potential to serve as a new platform for the development of next-generation high-performance UV PDs. [19][20][21][22][23][24][25][26][27]…”
Section: Photoconductive Transport-mechanism and Performance Comparis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by integration with emerging high-efficiency electrode materials, the GaN-based microwires structures with trap-assisted transport paths hold the potential to serve as a new platform for the development of next-generation high-performance UV PDs. [19][20][21][22][23][24][25][26][27]…”
Section: Photoconductive Transport-mechanism and Performance Comparis...mentioning
confidence: 99%
“…[16][17][18] Furthermore, there is active research in progress for the development of high-performance devices using low-dimensional GaN materials by integrating emerging next-generation electrode materials and other semiconductor materials such as Mxene, graphene, silver nanowires (NWs), and MoS 2 . [19][20][21][22][23][24][25][26][27] Compared with their planar layer counterparts, 1D nano/microstructures like nano/microwire (MW), -tube,ribbon, and -belt-based UV PDs have shown superior sensitivity and photoconductive gain as a result of their large active area to receive light sources and the limitation of effective conductive channels to transport charge carriers. [28][29][30][31] Recently, Shuti Li et al reported UV PDs based on horizontally ordered GaN MW arrays with excellent potential for the efficient enhancement of the surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Fabricating nanoporous GaN (porous-GaN) is a promising approach to improve the light absorption due to large specific surface area and photo trap effect of porous structures [ 96 ]. As shown in Figure 6 b, Qin’s group prepared a novel self-powered UV photodetector based on p-type cobalt phthalocyanine (CoPc)/n-type porous-GaN vertical heterojunction through a thermal vapor deposition method [ 97 ]. At 0 V bias, the device exhibits a photoresponsivity of 588 mA/W, a detectivity of 4.8 × 10 12 Jones, and a linear dynamic range of 79.5 dB under 365 nm 9 μW/cm 2 light illumination, which displays an upper level among the reported work.…”
Section: Improving the Performance Of Self-powered Uv Photodetectors ...mentioning
confidence: 99%
“…Copyright 2021 The Royal Society of Chemistry; ( b ) high-performance self-powered ultraviolet photodetector based on nano-porous GaN and CoPc p–n vertical heterojunction. Reprinted with a permission from reference [ 97 ]. Copyright 2019 Multidisciplinary Digital Publishing Institute; ( c ) Al x Ga 1-x N-based back-illuminated solar-blind photodetectors with external quantum efficiency.…”
Section: Figurementioning
confidence: 99%
“…The interaction of spins with heat currents was studied in MPc (M = Mn, Fe, Co, Ni) molecular devices and the MnPc device exhibits a perfect SFE and thermal-SFE as well as sizeable GMR/thermal GMR effects [12]. The metal phthalocyanine has also been used in photodetectors and nano-porous GaN and CoPc p-n vertical heterojunction bonded as a high-performance self-powered ultraviolet photodetector [13].…”
Section: Introductionmentioning
confidence: 99%